2022
DOI: 10.3390/su142214728
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Artificial Reef on the Structure and Function of Sediment Bacterial Community

Abstract: The bacterial community in sediment is sensitive to artificial disturbance, and they respond differently to human disturbance, such as changing the nutrient cycling and energy flow in marine ecosystems. However, little is known about the dynamics and distribution of bacterial community structures in marine sediments and potential biogeochemical functions during the long-time succession in marine ranching. In the present study, we compared the dynamics of the bacterial composition and potential biogeochemical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…Ref. [113] used metagenomics to determine the bacteria present in marine benthic samples taken from beneath one-and ten-year-old concrete reefs in the Beibu Gulf, China. They found that Rickettsiales, Moraxellaceae, and Acinetobacter were enriched in 10-year-old samples, while Francisella was enriched in the one-year-old reef sediments.…”
Section: Artificial Reefs: a Special Casementioning
confidence: 99%
“…Ref. [113] used metagenomics to determine the bacteria present in marine benthic samples taken from beneath one-and ten-year-old concrete reefs in the Beibu Gulf, China. They found that Rickettsiales, Moraxellaceae, and Acinetobacter were enriched in 10-year-old samples, while Francisella was enriched in the one-year-old reef sediments.…”
Section: Artificial Reefs: a Special Casementioning
confidence: 99%